Implementation of connection scan algorithm in tourism intermodal transportation journey planner: a case study - Vertic Eridani Budi Darmawan; Yuh Wen Chen (Universitas Serang Raya, 2020)
Accessibility to tourist destinations is an important component in a tourism system, especially for natural tourist destinations located in suburban areas. Good linkage of travel information and physical connections with local transportation services for intercity travel can facilitate more people to travel and promote national tourism destinations. This research takes the popular national tourism destinations and their public transportation service in Taiwan as a research object due to the unavailability of integrated public transport information service. Free Independent Travelers (FIT) demand is growing. This research aims to integrate intermodal public transportation information to support FIT by proposing a seamless way journey planner. In this scenario, the journey planner requires timetable data as input. The Connection Scan Algorithm is used to find the earliest arrival time routes at their destinations. This journey planner is built in PHP language and can complement the official tourism travel information website by Tourism Bureau, MOTC. Hence, the FIT could get the quickest routes to reach the destinations without compiling the public transportation information provided independently.